Single or combined immune checkpoint inhibitors compared to first‐line platinum‐based chemotherapy with or without bevacizumab for people with advanced non‐small cell lung cancer - Ferrara, R; Imbimbo, M; Malouf, R; Paget-Bailly, S; Calais, F; Marchal, C; Westeel, V (Cochrane Collaboration, 2021)
Background Immune checkpoint inhibitors (ICIs) targeting the PD‐1/PD‐L1 axis have changed the first‐line treatment of people with advanced non‐small cell lung cancer (NSCLC). Single‐agent pembrolizumab (a PD‐1 inhibitor) is currently the standard of care as monotherapy in patients with PD‐L1 expression ≥ 50%, either alone or in combination with chemotherapy when PD‐L1 expression is less than 50%. Atezolizumab (PD‐L1 inhibitor) has also been approved in combination with chemotherapy and bevacizumab (an anti‐angiogenic antibody) in first‐line NSCLC regardless of PD‐L1 expression. The combination of first‐line PD‐1/PD‐L1 inhibitors with anti‐CTLA‐4 antibodies has also been shown to improve survival compared to platinum‐based chemotherapy in advanced NSCLC, particularly in people with high tumour mutational burden (TMB). The association of ipilimumab (an anti CTLA4) and nivolumab (PD‐1 inhibitor) has been approved by the US Food and Drug Administration (FDA) in all patients with PD‐L1 expression ≥1%. Although these antibodies are currently used in clinical practice, some questions remain unanswered, such as the best‐treatment strategy, the role of different biomarkers for treatment selection and the effectiveness of immunotherapy according to specific clinical characteristics.